Editorial - Padaria, R N (Indian Journal of Extension Education, 2020)
Online education has assumed great significance during the COVID-19 pandemic.Â Though it has offered great opportunities, the challenges too are galore. Besides technological perspective, it is highly pertinent to analyze the behavioural dimensionsÂ to understand as well as maneuver smooth transitioning of faculty and students from face-to-face classroom teaching to online virtual teaching and learning systems. It is important to focus upon capacity building of teachers for effective online teaching.Â According to research findings three factors are critical in online teaching, which include cognitive presence, teaching presence, and social presence. The cognitiveÂ presence highlights how to integrate concepts and theories into learning and discussions. The instructional design, discourse facilitation, structuring and planning of courses relate to teaching presence. The third important element is social presenceÂ which reflects the abilities of learners to project themselves socially. How they are able to bond with other members of the group as well as the instructor in order to have free discussions and exchange of ideas. The online teacher has to facilitate to fosterÂ development of community of inquiry where there is enhanced social interactions for better learning and greater satisfaction. A faculty should keep a beginner’s mindset toÂ be open for new learning of tools for online teaching; keep themselves upgraded in skill educational technology; promote active engagement of students through various means like discussion forums; and facilitate and utilize group communications toÂ make online teaching effective. I extend my sincere thanks to all the authors for making valuable contributions. I also extend sincere thanks to all the expert members in the editorial board. SpecialÂ thanks are extended to Dr M.S.Nain and Dr. Himanshu De for their painstaking efforts. Special thanks are extended to the President, ISEE; Dr US Gautam for providingÂ insightful thoughts and guidance in bring out this issue. Dr Bhanu Mishra deserves special thanks for making committed efforts in compiling and thorough editing of the papers.